Case literature analysis of Fournier’s gangrene caused by sodium-glucose protein-2 inhibitors - Liu, Hailing (Frontiers in Medicine, 2024)
Abstract: Objective To analyze the clinical characteristics and correlation of Fournier’s gangrene induced by sodium-glucose cotransporter protein-2 (SGLT-2) inhibitors, providing references for safe clinical drug use. Methods The CNKI, WanFang, and PubMed databases were searched, and relevant documents were collected and statistically analyzed. The basic information of patients, drug use information, adverse reactions and outcomes were extracted and analyzed. Results A total of 12 patients (8 males and 4 females) were included, with an average age of 55.6 years (ranging from 34 to 72 years). SGLT-2 inhibitors associated with Fournier's gangrene include empagliflozin (5 cases), dapagliflozin (5 cases), and canagliflozin (2 cases). Among them, 10 cases reported the time of first medication, ranging from 1 month to 6 years for the occurrence of adverse reactions. The most common concomitant drug was metformin (7 cases). Adverse reactions mainly manifested as redness, swelling and pain in the buttocks, perineum, perianal, scrotum and other positions, accompanied by an increased white blood cell count. Following surgery and antibiotic treatment, all patients showed improved. Conclusion Fournier’s gangrene induced by SGLT-2 inhibitors is rare. If patients using SGLT-2 inhibitors are suspected of having Fournier’s gangrene, it is recommended to discontinue the drugs immediately and initiate active treatment to ensure clinical safety.